Selection of Thermoelectric Materials to Improve the Efficiency of SOFC Devices Through Cogeneration. (2015) - Segarra, M.; Espiell, F.; Morales, M.
Abstract: Fuel Cells (FCs) are electrochemical devices that directly convert the chemical energy of a reaction into electrical energy. The energy conversion processes theoretically remain unaltered as long as the fuel and oxidant feed the device. A single cell consists of two electrodes (anode and cathode), and an electrolyte, which can be a solid oxide that transports ions, thus becoming a SOFC (solid oxide fuel cell). To achieve the oxide-ion conductivity necessary to ensure high enough power density, these fuel cells require high and/or intermediate temperatures (over 500 °C).The fuel conversion efficiency of conventional SOFCs is usually about 50%. Thus, much of the chemical energy converts into waste heat energy, whereas thermoelectric materials can generate electricity from the waste heat. Some studies have been published in which the cathode of the fuel cell has been replaced by a thermoelectric material, and different simulation studies have been performed in which the waste heat is harnessed by thermoelectrics in a heat exchanger. The aim of this work is to provide an overview of thermoelectric materials that could help to select the best one to harness the heat evolved by a SOFC device to increase its efficiency. Data has been collected for different thermoelectric materials, including their thermoelectric performance, operation temperature range, and cost. To choose a thermoelectric material, it is necessary to define a performance parameter that allows us to classify all the different materials by means of their performance. Among the best, operating temperature and cost will turn into constraints that must be met to find the best material that suits the characteristics of a SOFC operation environment, and that really can be used in combination with the fuel cell.